2013
DOI: 10.1021/ma302577e
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Evaluation of Random Copolymer Mimesis of Homogeneous Antimicrobial Peptides

Abstract: Polymeric synthetic mimics of antimicrobial peptides (SMAMPs) have recently demonstrated similar antimicrobial activity as natural antimicrobial peptides (AMPs) from innate immunity. This is surprising, since polymeric SMAMPs are heterogeneous in terms of chemical structure (random sequence) and conformation (random coil), in contrast to defined amino acid sequence and intrinsic secondary structure. To understand this better, we compare AMPs with a ‘minimal’ mimic, a well characterized family of polydisperse c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 69 publications
2
99
0
Order By: Relevance
“…The preference for these nylon-3 polymers to generate cubic phases at a high PE content of 60–80% points to a mechanism of selectivity for bacterial membranes, such as that of E. coli , which has a composition of PG/PE/CL ≈ 20/70/10–20/75/5 [58,63]. We note that this mechanism is cognate with those observed for natural and synthetically derived AMPs [7,19,20,49,95]. …”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…The preference for these nylon-3 polymers to generate cubic phases at a high PE content of 60–80% points to a mechanism of selectivity for bacterial membranes, such as that of E. coli , which has a composition of PG/PE/CL ≈ 20/70/10–20/75/5 [58,63]. We note that this mechanism is cognate with those observed for natural and synthetically derived AMPs [7,19,20,49,95]. …”
Section: Resultsmentioning
confidence: 55%
“…5). The five following compositions were used to model PE-rich prokaryotic membranes: DOPG/DOPE/CL = 10/80/10 and 20/60/20, DOPG/DOPE/DOPC = 20/80/0 and 20/60/20, and DOPS/DOPE = 20/80 [7,49,93]. The first three of these membranes served specifically to mimic that of E. coli , which is composed of PG/PE/CL ≈ 20/70–75/5–10 [58,63].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have identified a strong correlation between the formation of NGC and AMP-induced membrane destabilization mechanisms (11, 12, 3437). NGC is also known as saddle-splay curvature, on which a surface curves upwards in one direction and downward in the perpendicular direction.…”
Section: Resultsmentioning
confidence: 96%
“…Kuroda, Wong, L. Yang and co-workers conducted a mechanistic comparison between AMPs and synthetic mimics of antimicrobial peptides (SMAMPs), with regard to the cationic and hydrophobic content [40]. They found out that both systems can form similar amounts of negative Gaussian curvatures (NGCs).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%